The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.5301/hip.2012.9075
|View full text |Cite
|
Sign up to set email alerts
|

Superior 11-Year Survival but Higher Polyethylene Wear of Hydroxyapatite-Coated Mallory-Head Cups

Abstract: Hydroxyapatite (HA) coating of implant surfaces is believed to improve longevity of uncemented total hip arthroplasty (THA). However; it is speculated that HA particles may cause third body wear of the polyethylene (PE) liner with subsequent osteolysis and aseptic loosening of implants. We performed a retrospective comparison of two patient populations with cementless Mallory-Head acetabular components. The patients were identified in the Danish hip arthroplasty Registry (DHR); 77 patients had HA-coated cups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
15
1
Order By: Relevance
“…In comparison with those data, our analysis revealed that the linear wear rate of highly cross-linked polyethylene was very low. No risk factors for high wear rates were found, although the type of porous coating, type of zirconia, age, body weight, cup inclination angle, and polyethylene thickness were frequently addressed in previous studies [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 89%
“…In comparison with those data, our analysis revealed that the linear wear rate of highly cross-linked polyethylene was very low. No risk factors for high wear rates were found, although the type of porous coating, type of zirconia, age, body weight, cup inclination angle, and polyethylene thickness were frequently addressed in previous studies [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 89%
“…But register and long-term clinical studies also reveal discrepancies regarding the performance of HA-coated hip prostheses. Gottliebsen et al (2012) reported superior survival of HA-coated Mallory-Head cups in their 11-year follow-up clinical study, but a higher annual PE wear rate in the HA group than in the non-HA group. This was a retrospective non-randomized study and the mean age in the HA group was 6 years younger than that in the non-HA group, indicating that a higher activity level could contribute to the PE wear.…”
Section: Discussionmentioning
confidence: 94%
“…On the contrary, our results show a clear tendency of less migration and lower wear rates in the HA-coated group. Gottliebsen et al (2012) presented 11-year follow-up data comparing HA-coated and non-HA-coated Mallory-Head cups. They concluded that PE wear was increased in HA-coated cups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these coatings may dislodge during implantation or cyclic loading, leading to the generation of debris capable of inducing osteoclast activation and synovial cyst formation, as well as the acceleration of bearing component wear, which may result in periprosthetic osteolysis (Grandjean‐Laquerriere, Laquerriere, Guenounou, Laurent‐Maquin, & Phillips, ; Lange et al, ; Nehme, Oakes, Marcheix, Gomez‐Brouchet, & Puget, ; Otsuka, Kojima, & Mutoh, ; Sabokbar et al, ). Clinical studies performed by Stilling et al and Gottliebsen et al demonstrated the impact of hydroxyapatite particulate on the in vivo wear behavior of polyethylene acetabular liners after more than 10 years of in vivo implantation (Gottliebsen, Rahbek, Ottosen, Soballe, & Stilling, ; Stilling, Rahbek, & Soballe, ).…”
Section: Introductionmentioning
confidence: 99%